Edukasi Kepada Masyarakat Kelurahan Sompe Untuk Meningkatkan Minat Investasi - Siardin Andi Djemma; Indra Heri Rukmana; Akbar; Asrul Jaya; Andi Meilanie Majid (Compile Journal of Society Service, 2024)
One way to increase wealth and protect it from possible inflation is to invest, and this is very important for people to achieve a decent life (financial freedom), especially in meeting their needs in retirement. In general, Indonesians who have guaranteed pension funds are those who work as civil servants, police and military. But in fact, especially in Sompe village, most people are farmers and entrepreneurs, 36 per cent of the 4,210 population. With this in mind, it is necessary to provide advice that educates the community to increase their awareness of investment interest. In Indonesia, investment interest is still dominated by young people.